Anomalous geothermal regime, seismic, and gravitational landslide activity in the northeastern part of the Black Sea continental slope. - Verzhbitsky, Evgeny V; Lobkovsky, Leopold I; Pokryshkin, Alexander A; Soltanovsky, Igor I (PANGAEA, 2005)
According to the World Ocean Program in the northeastern part of the continental slope of the Black Sea geothermal, seismologic and seismic studies were carried out. An analysis of heat flow distribution allowed to distinguish a negative geothermal anomaly near the Dzhubga area, where the Russia-Turkey pipeline was being constructed. During seismological observations (August-September 1999, September 2001) more than 1200 seismic events were recorded. They proved high tectonic activity of the region under study, which stimulates gravitational sediment transport on the continental slope. The seismo-acoustic survey carried out in the area of the geothermal anomaly revealed no reflecting horizons within the sedimentary cover. This may be related to turbidite-landsliding processes. Results of modeling of the heat flow anomaly showed that it had originated approximately 1000 years ago due to a powerful landslide. This also suggests a possibility of an avalanche displacement of sedimentary masses in the area of the pipeline at present.
(Table 1) Results of geothermal measurements in the Black Sea 2000 and 2001 expeditions
Keywords: Archive of Ocean Data; ARCOD; Black Sea; Conductivity, thermal; Element analyser isotope ratio mass spectrometer (EA-IRMS); Heat flow; Heat flow, standard deviation; Temperature (thermal) gradient; TGC; Thermal conductivity meter; Thermistor Gravity Corer; VLPS-BS-00/01-1; VLPS-BS-00/01-2; VLPS-BS-00/01-3; VLPS-BS-00/01-4; VLPS-BS-00/01-5; VLPS-BS-00/01-6; VLPS-BS-00/01-7; VLPS-BS-00/01-8